d-Ala:d-Ala Ligase Gene Flanking the vanC Cluster: Evidence for Presence of Three Ligase Genes in Vancomycin-Resistant Enterococcus gallinarum BM4174 - Ambúr, Ole-Herman (American Society for Microbiology, 2002)
An open reading frame located 230 nucleotides downstream from the stop codon of vanS(c) and in the opposite direction relative to the other genes of the vanC cluster was identified in Enterococcus gallinarum BM4174. This gene (designated ddl2) encoded a protein of 343 amino acids that had significant predicted structural similarity to d-Ala:d-Ala ligases and displayed 33 and 35% amino acid identity to VanC-1 and the previously reported partial sequence of Ddl from E. gallinarum, respectively. Biochemical characterization by thin-layer chromatography confirmed that Ddl2 is a d-Ala:d-Ala ligase with no detectable d-Ala:d-Ser ligase activity. The vancomycin dependence of Enterococcus faecalis BM4320 (ddl mutant) was lost on electroporation of a plasmid construct expressing ddl2 constitutively. The latter strain was able to grow in the absence of vancomycin, and peptidoglycan precursor analysis under the same conditions indicated the synthesis of pentapeptide[d-Ala] as the main precursor, confirming the activity of Ddl2 in vivo. Expression of ddl and ddl2 in BM4174 was tested by reverse transcription-PCR: results suggested that both d-Ala:d-Ala ligases were expressed concomitantly. Our findings indicate that vancomycin-resistant E. gallinarum BM4174 is likely to express one d-Ala:d-Ser and two d-Ala:d-Ala ligase genes.